MARRIED BY ACCIDENT PONOROGO DI MASA PANDEMI: FAKTOR, HUKUM DAN SOLUSI ALTERNATIF - Dina Sakinah Siregar; Munawwir Ramadhan (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This article uses empiric and sociologic research. The method is qualitative-descriptive. It will analyze, discuss, understand, and opinions from the researcher. It uses Islamic and civil law as the primary literature. It takes library research and content analysis. This research discusses the laws of married by accident, the factors, and the solutions for Ponorogo society. The result shows many Married by Accident cases among youths in Ponorogo. Data from Ponorogo Religious Courts showed eight-fold cases over 2019-2021. The researcher will give thoughts on the solution to accidents and minimize them more. The writer gives some solutions are studying more about religion, talking close to Allah SWT, who gives knowledge about sex education, staring sight down, paying attention to clothes, avoiding khalwat and ikhtilath, doing ta’aruf, getting better role from family, school, and society, and fasting